Analysis of Entrepreneurial Education-Study of the Configuration of the Entrepreneurial Identity through the Acquisition of Crucial Transversal Competences for Future University Students - Macarena Donoso-González; Inmaculada Pedraza-Navarro; Leonardo Palferro-Fernández (MDPI AG, 2022)
Faced with the continuous changes that today's society presents, educational policies place entrepreneurial education and, therefore, the promotion of the entrepreneurial spirit, as the axis on which to articulate effective responses for the current socio-educational context. The need to train students in key aspects that will enable them to face the main difficulties that future labor and social future bring is the focus of attention of the educational environment. In this sense, we set out to find out how entrepreneurial education affects the identity formation of pre-university students in the Spanish context through the pedagogical and environmental factors present in an entrepreneurial education programme. The methodology used is based on qualitative research, which under an interpretative approach, has been assisted by quantitative and evaluative research on educational programmes, in order to try to respond to research objectives. The findings of this research lead us to consider entrepreneurial education in the pre-university environment as effective for the configuration of entrepreneurial identity in students, which facilitates an encouraging future for university students participating in these programmes, who will present an improved entrepreneurial identity that enables them to face forthcoming social, economic and labor reconfigurations.